Cambio y continuidad : el Pacto Andino en la historia contemporánea - Veliz, Claudio (Estudios Internacionales, 1971)
This paper seeks to determine the factors of change and continuity that modify, guide, attenuate, or revitalize, the political and economic activity of the countries that signed the Cartagena Agreement. We suggest that there are factors in our contemporary situation classified as relative continuities in our historical development and that they could acquire very great importance at this time by reinforcing and invigorating certain factors of change that would otherwise have a more attenuated effect. We propose, with a certain hesitation that is difficult to avoid, that the Andean Pact is in a situation of unparalleled opportunity in the contemporary world, both due to the continuities that back it up, and due to the nature of the domestic and external changes that modify it.